2018
DOI: 10.1002/rcr2.315
|View full text |Cite
|
Sign up to set email alerts
|

Methimazole‐induced ANCA‐associated vasculitis with diffuse alveolar haemorrhage

Abstract: Antineutrophil cytoplasmic antibody (ANCA)‐associated vasculitis (AAV) caused by methimazole (MMI) is known to be relatively rare; therefore, the optimal therapeutic approach for these cases remains to be established. A 59‐year‐old man who was treated with MMI for a diagnosis of Graves’ disease was referred to our hospital because of progressive haemoptysis. The patient was diagnosed with diffuse alveolar haemorrhage (DAH) secondary to AAV based on increased inflammatory reactions with positive myeloperoxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“… CD, HF Turan 2020 [ 21 ] abciximab HP, MI clopidogrel, aspirin, heparin. CD Seto 2011 [ 22 ] bevacizumab branch retinal vein occlusion, gastric cancer none diminish the regenerative capacity of endothelial cells Tahir 2015 [ 23 ] alemtuzumab RF, Alport syndrome, renal transplantation, methy prednisolone, chlorpheniramine, paracetamol Sepsis Ohtsuka 1997 [ 24 ] Propylthiouracil GD none AAV Yamauchi 2003 [ 25 ] Propylthiouracil GD, HP, hyperlipidaemia, Simvastatin, ethy icosapentate, amlodipine besilate AAV El-Fakih 2008 [ 26 ] Propylthiouracil GD none AAV Arai 2018 [ 27 ] methimazole GD none AAV Perri 2007 [ 28 ] azathioprine IPF, HP, CKD, bladder cancer Prednisone, beclomethasone inhalations, nadolol and hydrochlorothiazide Myelosuppression, thrombocytopenia, pneumonia Tanawuttiwat 2010 [ 29 ] Amiodarone AF, HP, AKI, rhabdomyolysis, intravenous hydration, metoprolol and warfarin PT, A...…”
Section: Discussionmentioning
confidence: 99%
“… CD, HF Turan 2020 [ 21 ] abciximab HP, MI clopidogrel, aspirin, heparin. CD Seto 2011 [ 22 ] bevacizumab branch retinal vein occlusion, gastric cancer none diminish the regenerative capacity of endothelial cells Tahir 2015 [ 23 ] alemtuzumab RF, Alport syndrome, renal transplantation, methy prednisolone, chlorpheniramine, paracetamol Sepsis Ohtsuka 1997 [ 24 ] Propylthiouracil GD none AAV Yamauchi 2003 [ 25 ] Propylthiouracil GD, HP, hyperlipidaemia, Simvastatin, ethy icosapentate, amlodipine besilate AAV El-Fakih 2008 [ 26 ] Propylthiouracil GD none AAV Arai 2018 [ 27 ] methimazole GD none AAV Perri 2007 [ 28 ] azathioprine IPF, HP, CKD, bladder cancer Prednisone, beclomethasone inhalations, nadolol and hydrochlorothiazide Myelosuppression, thrombocytopenia, pneumonia Tanawuttiwat 2010 [ 29 ] Amiodarone AF, HP, AKI, rhabdomyolysis, intravenous hydration, metoprolol and warfarin PT, A...…”
Section: Discussionmentioning
confidence: 99%
“…Other than vasculitis, commonly cited complications include arthritis, agranulocytosis, autoimmune hepatitis, cholestasis, hypoglycemia, pancreatitis, and hypoprothrombinemia [3]. The vasculitic process often involves kidneys and lungs [4, 5]. Other target organs include joints, muscles, nerves, or skin, with variable clinical presentation [3, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding vasculitis, a study reported an adverse reaction event of Methimazole-induced vasculitis [46]. Regarding hepatic failure, liver injury, and traumatic liver injury, existing research indicates that Methimazole can cause hepatotoxicity [44].…”
Section: Predicting the Drug-adr Associations For Methimazole And Pro...mentioning
confidence: 99%